APPLICATION OF RESPONSIBILITY ACCOUNTING AS A COST CENTER PERFORMANCE ASSESSMENT TOOL AT Sutan RAJA AMURANG HOTEL - Martha Suhardiyah; Ferry Hariawan; Widiar Onny Kurniawan; Tarisya Maulidya Wati; Gintan Regita Maharani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The achievement of an enterprise may be measured with the aid of using the capacity of control to layout the proper approach and enforce it domestically to gain results. The use of legal responsibility accounting in a enterprise can assist gain this goal. Research carried out at the Stan Raja Amran Hotel the usage of descriptive qualitative strategies indicate that the resort applies accountable accounting however is not maximized in phrases of organizational structure, finances planning, accounts categories and reporting accounting. However, the cost category. King's booth Amran Hotel's price middle overall performance is notable in each planning and price manipulation process.